Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 206764 by mustafazaheen last updated on 24/Apr/24

Answered by A5T last updated on 24/Apr/24

f(g(−3))=f((√(−3)))=f((√3)i)=((√3)i)^2 =−3

f(g(3))=f(3)=f(3i)=(3i)2=3

Commented by JDamian last updated on 24/Apr/24

(√(−3 ))≠ 3i  (√(−3)) = (√3)i  ⇒ ((√3)i)^2  = −3    because  g(x) = f^(−1) (x) ⇒ f○g = g ○f = x

33i3=3i(3i)2=3becauseg(x)=f1(x)fg=gf=x

Commented by mr W last updated on 24/Apr/24

for x∈R  f_1 (x)=((√x))^2  is valid for x≥0  f_2 (x)=x  f_1 (−3)≠−3, because f_1 (−3) is not defined.   f_2 (−3)=−3

forxRf1(x)=(x)2isvalidforx0f2(x)=xf1(3)3,becausef1(3)isnotdefined.f2(3)=3

Commented by A5T last updated on 24/Apr/24

Yea, it depends on the domain.

Yea,itdependsonthedomain.

Answered by A5T last updated on 24/Apr/24

f(g(x))=((√x))^2 =x⇒f(g(−3))=−3

f(g(x))=(x)2=xf(g(3))=3

Answered by aba last updated on 29/Apr/24

−3

3

Terms of Service

Privacy Policy

Contact: info@tinkutara.com